A Critique on the Methods of Teaching Verbs of Motio in Russian Language in Iranian Universities - Rezvan Hasanzadeh (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The present article reviews and examines the methods of teaching Russian motion verbs and provides quality strategies for teaching this category of the Russian language in our country's universities within the framework of the Russian language teaching course as a foreign language. The results of the present article, which are the result of studying new methods of teaching the Russian language, show that one of the most important measures that should be done by the teacher, especially at the beginning of the teaching, is to create a correct and objective image of Russian language as a foreign language and goals. The main thing is in the minds of language learners. Learners should know from the beginning that the language they are about to learn, especially at the beginning, will be slightly different from the languages of the languages in which it is considered their mother tongue. Therefore, in the present article, based on the teaching of motion verbs in the Russian language and the many problems that language learners have in the practical and applied learning of this language category, qualitative solutions to the teaching of motion verbs are proposed. The research method in this article is descriptive and analytical and it uses the data and results of teaching methods used in lesson sessions related to teaching motion verbs over several years.